2018
DOI: 10.1038/s41598-018-30114-4
|View full text |Cite
|
Sign up to set email alerts
|

Human-origin probiotic cocktail increases short-chain fatty acid production via modulation of mice and human gut microbiome

Abstract: The gut bacteria producing metabolites like short-chain fatty acids (SCFAs; e.g., acetate, propionate and butyrate), are frequently reduced in Patients with diabetes, obesity, autoimmune disorders, and cancers. Hence, microbiome modulators such as probiotics may be helpful in maintaining or even restoring normal gut microbiome composition to benefit host health. Herein, we developed a human-origin probiotic cocktail with the ability to modulate gut microbiota to increase native SCFA production. Following a rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(179 citation statements)
references
References 68 publications
(69 reference statements)
7
169
0
3
Order By: Relevance
“…More profound changes in the gut microbiota composition may occur after administration of multiple probiotic strains, combined or not with prebiotics, as previously shown for the VSL#3 cocktail that contains 8 different strains (15). Nagpal et al (59) also recently reported that a new cocktail of 10 humanorigin lactic acid bacteria modulates gut microbiota composition within a few hours and up to 10 d, which was accompanied by the increase of SCFA production. The authors used a dose of 10 11 cfu/gavage, whereas in the current study, a dose of 10 9 cfu/gavage has been used, suggesting that differences in gut microbiota modulations between both studies could be related to the dose.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…More profound changes in the gut microbiota composition may occur after administration of multiple probiotic strains, combined or not with prebiotics, as previously shown for the VSL#3 cocktail that contains 8 different strains (15). Nagpal et al (59) also recently reported that a new cocktail of 10 humanorigin lactic acid bacteria modulates gut microbiota composition within a few hours and up to 10 d, which was accompanied by the increase of SCFA production. The authors used a dose of 10 11 cfu/gavage, whereas in the current study, a dose of 10 9 cfu/gavage has been used, suggesting that differences in gut microbiota modulations between both studies could be related to the dose.…”
Section: Discussionmentioning
confidence: 67%
“…Nagpal et al . (59) also recently reported that a new cocktail of 10 human‐origin lactic acid bacteria modulates gut microbiota composition within a few hours and up to 10 d, which was accompanied by the increase of SCFA production. The authors used a dose of 10 11 cfu/gavage, whereas in the current study, a dose of 10 9 cfu/gavage has been used, suggesting that differences in gut microbiota modulations between both studies could be related to the dose.…”
Section: Resultsmentioning
confidence: 88%
“…Fan et al observed that bacteroides including Blautia producta and Bacteroides thetaiotaomicron directly affect C. albicans colonization through SCFAs 2 . Our recent studies found that the probiotics interventions increase the SCFAs production by modulating human and mice gut microbiome 92 . Therefore, future studies including characterization of probiotic or commensal bacteria to enhance the abundance of SCFA levels may form a novel approach to prevent and treat C. albicans colonization and subsequent pathogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Equal amount of snap frozen cecal content was weighed, dissolved in HPLC grade water and supernatants were collected after centrifugation (12,000 g, 10 min), while processing on ice. Concentrations of SCFAs (acetate, propionate and butyrate) were determined using a HPLC system (Waters-2695 Alliance HPLC system, Waters Corporation, Milford, MA, USA) equipped with Aminex HPX-87H column (Bio-Rad Laboratories, Hercules, CA) and DAD detector (210 nm), and eluting with H 2 SO 4 (0.005 N) mobile phase with a flow rate of 0.6 ml/min at 25°C, as described elsewhere 92 .…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, we anticipate the emerging scenario wherein GMHI could aid the proper selection of healthy donors and stool samples. To this point, GMHI could further facilitate future efforts to define design-principles of a healthy gut microbiome and to establish rational strategies for restoring or maintaining wellness in the form of probiotic 'cocktail' communities 68,69 .…”
Section: Discussionmentioning
confidence: 99%